Studi Kelayakan Bisnis Sate Padang: Analisis Pasar Dan Proyeksi Keuangan Untuk Keberlanjutan Usaha - Lestari Diah Wulandari; Yuni Saputri Maulidiyah; Dwi astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The culinary industry in Indonesia, particularly in the traditional food sector, continues to show significant development. One of the distinctive culinary delights with great potential is Sate Padang, known for its spicy and savory flavor. This research aims to evaluate the business feasibility of Sate Padang from various aspects, including market analysis, technical aspects, and financial projections. The methods used include a qualitative approach to analyze consumer preferences and market trends, as well as a quantitative approach for calculating costs, revenues, and break-even points. The study results indicate that Sate Padang has very good prospects in the Indonesian culinary market, especially in major cities, with stable revenue projections and significant market growth. This business also has competitive advantages through quality taste, product innovation, and a unique consumer experience. With the right strategies, this business is expected to grow rapidly and reach the break-even point in a short time. Overall, the Sate Padang venture is deemed feasible to operate and has opportunities for sustainable development.